2014
DOI: 10.1179/2295333714y.0000000097
|View full text |Cite
|
Sign up to set email alerts
|

Myelofibrosis patients in Belgium: disease characteristics

Abstract: Objective: To date, only a small number of epidemiological studies on myelofibrosis have been performed. The current study aimed to characterize the myelofibrosis patient population in Belgium according to predefined disease parameters (diagnosis, risk categories, hemoglobin ,10 g/dl, spleen size, constitutional symptoms, platelet count, myeloblast count), with a view to obtaining a deeper understanding of the proportion of patients that may benefit from the novel myelofibrosis therapeutic strategies. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Most cases in the whole population (60%) and patients over 65 years (73%) were classified as intermediate-2 or high risk by IPSS. In this survey, up to 66% of patients were diagnosed with PMF, around 23% with post-ET MF, and 11% with post-PV MF [11].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Most cases in the whole population (60%) and patients over 65 years (73%) were classified as intermediate-2 or high risk by IPSS. In this survey, up to 66% of patients were diagnosed with PMF, around 23% with post-ET MF, and 11% with post-PV MF [11].…”
Section: Introductionmentioning
confidence: 78%
“…While HSCT is not recommended in elderly patients or patients with poor performance status or prohibitive comorbidities [13], all intermediate-2 or high-risk MF patients younger than 70 years and intermediate-1risk MF patients younger than 65 years with refractory and transfusion-dependent anemia, circulating blasts >2%, or adverse cytogenetics are candidates for HSCT [20]. Current reimbursement conditions in Belgium limit ruxolitinib use to intermediate-2 and high-risk MF patients, who often present splenomegaly and constitutional symptoms [11,21]. Recent studies showed that in intermediate-1 risk patients and in patients with constitutional symptoms without splenomegaly, ruxolitinib has a safety and efficacy profile consistent with that observed in higher-risk categories [22][23][24].…”
Section: Which Patients May Benefit From Ruxolitinib?mentioning
confidence: 99%
See 1 more Smart Citation
“…PMF is connected with a bad prognosis in assessment with the further classic BCR/ABL-negative myeloproliferative neoplasms, which may ultimately transform into acute leukemia [8].…”
Section: Discussionmentioning
confidence: 99%
“…PMF is associated with a worse prognosis in comparison with other classic BCR/ABL-negative myeloproliferative neoplasms, which may eventually culminate into acute leukemia (Cervantes et al, 2008;Devos et al, 2015). Yet survival may range from a few months to an excess of a decade.…”
Section: Discussionmentioning
confidence: 99%